2022
DOI: 10.3390/curroncol29030144
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Aromatase Activity Index, Gonadotropins and Estrone Are Associated with Frailty Syndrome in Post-Menopausal Women with Breast Cancer

Abstract: Frailty syndrome is associated with poor outcomes, morbidity and premature mortality. We performed a cross-sectional study to evaluate the presence of frailty syndrome based on Fried’s frailty phenotype in post-menopausal women with breast cancer. We further analyzed the association between frailty syndrome with geriatric assessments and the association with the concentration of gonadotropins LH and FSH, estrogens, androgens and the aromatase activity index in the blood. We enrolled 47 post-menopausal women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 86 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…Notably, almost 50% of the patients showed worsened frailty at 12 months of follow-up, while approximately 25% remained stable and 25% showed improvement of their frailty status. The latter effect (i.e., improvement) is not surprising, since frailty syndrome is a reversible condition mainly in the pre-frailty phase [ 27 , 28 ], and the women in our study were mostly (63.8%) prefrail (i.e., they met one or two frailty criteria) at baseline before receiving AROi treatment [ 23 ]. A recent longitudinal study (with one year of follow-up, as our study) in community-dwelling individuals found that one third of the frail older adults regressed to pre-frailty status, and 8.7% of the pre-frail older adults regressed to non-frailty status [ 29 ].…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Notably, almost 50% of the patients showed worsened frailty at 12 months of follow-up, while approximately 25% remained stable and 25% showed improvement of their frailty status. The latter effect (i.e., improvement) is not surprising, since frailty syndrome is a reversible condition mainly in the pre-frailty phase [ 27 , 28 ], and the women in our study were mostly (63.8%) prefrail (i.e., they met one or two frailty criteria) at baseline before receiving AROi treatment [ 23 ]. A recent longitudinal study (with one year of follow-up, as our study) in community-dwelling individuals found that one third of the frail older adults regressed to pre-frailty status, and 8.7% of the pre-frail older adults regressed to non-frailty status [ 29 ].…”
Section: Discussionmentioning
confidence: 81%
“…Some of them received adjuvant chemotherapy ( n = 15; 31.9%) and radiotherapy ( n = 44; 93.6%) as per protocol of their adjuvant treatment. One month after the last radiotherapy session, all women had started adjuvant hormonal treatment with aromatase inhibitors (anastrozole or letrozole) [ 23 ]. The sociodemographic and oncology data are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations